PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA SMA - Ginting, Emi Katawarina; Ginting, Eva M (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2017)
This study aimed to know the effect of learning outcomes of students among the Problem Based Learning (PBL). This research is quasi- experimental study using control pre-test and pos-test design. The population study of class X SMA Swasta Harapan Bangsa Kuala. Techniques that used to gain a simple is cluster random sampling, with a sample of two classes, class X21 as an experimental class and class X-1 as an convensional class. The instruments of this study were the learning outcomes test in the form of an essay test as many as ten items, the affective, and psikomotoric was used observasion sheet. The analysis results showed that physics science process skills use Problem Based Learning (PBL) is different and showed better result compared with conventional learning model.